Social Media as Grassroot Platform Voice to Respond to Issues in Surakarta Case: @gibran_tweet - Anggreyani, Reysa; Suranto (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2023)
This Research explores the social media used to advocate the issues in Surakarta city, in this case, using the social media specific to the Twitter data of the mayor of Surakarta, Gibran Rakabuming Raka (@gibran_tweet). This Research uses Qualitative approach and analysis data with Qualitative Data Analysis Software (Q-DAS). This Research founds that First, The social media content dichotomy of account Gibran Rakabuming Raka as Mayor of Surakarta's dominance of social media as part of reports tolls shows that social media can access everyone to report about the social infrastructure and other problems in Surakarta City. Second, the activity of the account of Gibran Rakbuming Raka focuses only on Surakarta city content. Third, the narration dominance with words related to the location Surakarta or Solo, indicated that the content of Gibran Rakabuming Raka as mayor of Surakata or Solo refers to the specific area in Solo or Surakarta, shows that the content dominance for local content of solo or Surakarta.